2011
DOI: 10.1073/pnas.1010814108
|View full text |Cite
|
Sign up to set email alerts
|

Pack- Mutator –like transposable elements (Pack-MULEs) induce directional modification of genes through biased insertion and DNA acquisition

Abstract: In monocots, many genes demonstrate a significant negative GC gradient, meaning that the GC content declines along the orientation of transcription. Such a gradient is not observed in the genes of the dicot plant Arabidopsis. In addition, a lack of homology is often observed when comparing the 5′ end of the coding region of orthologous genes in rice and Arabidopsis. The reasons for these differences have been enigmatic. The presence of GC-rich sequences at the 5′ end of genes may influence the conformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 47 publications
4
95
0
Order By: Relevance
“…In addition, fewer reinsertions occurred in repetitive regions, including telomeres and long terminal repeat retrotransposons, which is consistent with the target specificity of MULEs in plants for low copy sequences (Raizada et al, 2001;Liu et al, 2009). Previous studies showed that MULEs or PackMULEs prefer to insert into the 59 region of genes, with decreasing frequencies toward the 39 region (Dietrich et al, 2002;Liu et al, 2009;Jiang et al, 2011). Among cv Nipponbare's four copies of Os3378, only one of them is located in proximity to a gene (in the 59 region) (Gao, 2012), which is insufficient to determine whether this preference is similar to other MULEs.…”
Section: Comparison Of Target Specificity Between Rice and Yeastsupporting
confidence: 59%
“…In addition, fewer reinsertions occurred in repetitive regions, including telomeres and long terminal repeat retrotransposons, which is consistent with the target specificity of MULEs in plants for low copy sequences (Raizada et al, 2001;Liu et al, 2009). Previous studies showed that MULEs or PackMULEs prefer to insert into the 59 region of genes, with decreasing frequencies toward the 39 region (Dietrich et al, 2002;Liu et al, 2009;Jiang et al, 2011). Among cv Nipponbare's four copies of Os3378, only one of them is located in proximity to a gene (in the 59 region) (Gao, 2012), which is insufficient to determine whether this preference is similar to other MULEs.…”
Section: Comparison Of Target Specificity Between Rice and Yeastsupporting
confidence: 59%
“…Pack-MULEs have a propensity to transduplicate GC regions of genes and they tend to insert into the 5′ ends of genes. In some cases, PackMULEs end up constituting the 5′ end of genes, presumably because after insertion, transcript initiates from within the element, a phenomenon that has been documented in both maize and rice (135,138). This raises the intriguing possibility that the observed GC gradient in monocots is at least in part a consequence of millions of years of sequence capture and deposition of GC-rich sequences by Pack-MULEs into the 5′ end of genes.…”
Section: Pack-mulesmentioning
confidence: 95%
“…There are approximately 3,000 rice Pack-MULEs that collectively contain approximately 1,000 fragmented or whole-gene sequences (Jiang et al, 2004). There are a similar number of Helitrons (approximately 2,800) in maize (Zea mays; Du et al, 2009) but only 46 PackMULEs in Arabidopsis (Jiang et al, 2011). This difference potentially reflects the historical difference in TE activity.…”
Section: Mechanisms Of Gene Duplicationmentioning
confidence: 97%